A ternary amorphous compound, modified positive electrode material, and preparation method and application thereof
Patent Information
- Application Number
- CN202611088357.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-22
AI Technical Summary
[0005]本发明的目的是针对现有技术中,钠电层状氧化物正极材料空气稳定性差、界面副反应、单一包覆改性效果有限的问题,提供一种三元非晶化合物、改性正极材料及其制备方法、应用,尤其是一种低温熔融的三元非晶化合物实现近表层高熵离子掺杂结合外层非晶态化合物包覆的复合改性的钠电层状氧化物正极材料及其制备方法
本发明所制备得到的三元非晶化合物复合改性钠电层状氧化物正极材料能够协同提升。
Smart Images

Figure CN122599426B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of sodium-ion battery cathode materials, specifically relating to a ternary amorphous compound, a modified cathode material, its preparation method, and its applications. In particular, it relates to a composite modified sodium-ion battery layered oxide cathode material with a ternary amorphous compound exhibiting low-temperature melting characteristics, achieving near-surface high-entropy ion doping combined with an outer amorphous compound coating, and its preparation method. Background Technology
[0002] Sodium-ion batteries possess advantages such as abundant resources and low cost, demonstrating enormous application potential in fields such as large-scale energy storage. Sodium-ion battery layered oxide cathode materials (such as NaNi) 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, Na 2 / 3 Ni 1 / 3 Mn 2 / 3 Layered oxide cathode materials (SO₂, etc.) have become an important research direction for sodium-ion batteries due to their high specific capacity and operating voltage. However, sodium-ion battery layered oxide cathode materials have obvious defects during charge-discharge cycling: On the one hand, the material surface is prone to interfacial side reactions with the electrolyte, forming an unstable SEI film, leading to electrolyte consumption and loss of active materials, which in turn causes capacity decay. At the same time, lattice distortion occurs during sodium insertion / extraction, and the stability of the material's crystal structure decreases after long-term cycling, ultimately resulting in poor cycle performance. On the other hand, sodium-ion battery layered oxide cathode materials have poor air stability and readily react with H₂O and CO₂ in the air, causing sodium to be released from the material surface to form sodium hydroxide and sodium carbonate residues, which deteriorate the material's capacity, cycle performance, and other electrochemical properties.
[0003] To address these issues, existing technologies often employ coating modification methods. However, single coating materials have limitations: for example, while Al2O3 coating can suppress interfacial side reactions between the material and the electrolyte, it cannot improve the material's air stability; nano-calcium carbonate has numerous hydroxyl groups on its surface, making it highly susceptible to absorbing moisture from the air and exhibiting hydrophilicity. Furthermore, its small particle size and large specific surface area make it difficult to disperse and prone to agglomeration, limiting its effectiveness as a coating agent for cathode materials.
[0004] Therefore, developing a coating material that combines excellent interfacial structural stability and air stability, and using it for composite modification of cathode materials, is of great significance for improving the overall performance of sodium-ion layered oxide cathode materials. Summary of the Invention
[0005] The purpose of this invention is to address the problems of poor air stability, interfacial side reactions, and limited single-coating modification effects of sodium-electric layered oxide cathode materials in the prior art. This invention provides a ternary amorphous compound, a modified cathode material, its preparation method, and its applications. In particular, it describes a composite modified sodium-electric layered oxide cathode material and its preparation method that achieves near-surface high-entropy ion doping combined with outer amorphous compound coating using a low-temperature molten ternary amorphous compound.
[0006] This invention provides a ternary amorphous compound material with low-temperature melting characteristics. During high-temperature post-processing sintering, partially molten amorphous compound multi-atoms spontaneously dop into the near-surface crystal structure of the matrix material at high temperatures. Through the high-entropy-entropy stability mechanism of multi-atoms, the TM-O bond energy of the matrix material crystal structure is synergistically enhanced, suppressing interlayer slip caused by the large-volume phase transition of the O3 phase during phase transfer, and improving the stability of the material interface structure. At the same time, the remaining undoped ternary amorphous compound forms an amorphous coating layer under high-temperature melting, isolating the surface of the matrix material from H2O and CO2 in the air. Through the ternary amorphous compound that can melt at low temperatures, the composite modification of the near-surface high-entropy atomic doping of the matrix material synergistically with amorphous compound coating is achieved, ultimately realizing the simultaneous improvement of the material's cycle performance, interface structure stability, and air stability.
[0007] The objective of this invention can be achieved through the following methods: This invention provides a ternary amorphous compound, wherein the general chemical formula of the ternary amorphous compound is Si. x B y Bi z M (1-x-y-z) O2; where 0.4 < x ≤ 0.7, 0.1 < y < 0.3, 0.1 < z < 0.3; 0 < 1 - xyz ≤ 0.1; M is one or more of Al, Zn, Li, Mg, and Ca.
[0008] The preferred range for Si content is 0.45≤x≤0.7, and more preferably 0.45≤x≤0.65.
[0009] The preferred range for element B content is: 0.15≤y≤0.25.
[0010] The preferred range for Bi element content is: 0.15≤z≤0.25.
[0011] The preferred range for the content of element M is: 0.03≤1-xyz≤0.1.
[0012] The particle size of the obtained ternary amorphous compounds is 0.1-2 μm.
[0013] The softening temperature of the obtained ternary amorphous compound is between 350 and 620 °C.
[0014] The present invention provides a method for preparing the ternary amorphous compound, comprising the following steps: mixing the oxides of SiO2, B2O3, Bi2O3 and M doping elements in solid phase according to the required molar amounts of the elements in the chemical formula, calcining the mixture, and then cooling, quenching and pulverizing the resulting molten liquid to obtain the ternary amorphous compound.
[0015] The solid-phase mixing speed is 1200~1500 rpm, and the time is 30~60 min.
[0016] The calcination temperature is 1300~1500℃, and the time is 6~8 hours. The calcination is carried out in an air atmosphere.
[0017] Cooling and quenching involves pouring molten liquid into water. By rapidly cooling and quenching, the orderly arrangement of crystals is hindered at the microscopic level, resulting in an amorphous state.
[0018] The pulverization process includes grinding, ball milling, drying, and sieving. Grinding involves crushing the cooled and quenched product, followed by ball milling (wet ball milling), drying, and sieving to obtain a ternary amorphous compound with a particle size range that meets the requirements for use.
[0019] The ball mill speed is 80~150 rpm, and the time is 10~20 hours.
[0020] The drying temperature is 60~70℃, and the drying time is 20~24h.
[0021] This invention provides an application of the aforementioned ternary amorphous compound in the preparation of modified cathode materials. The application involves coating the ternary amorphous compound onto the surface of a cathode material matrix.
[0022] This invention provides a modified cathode material, wherein the modified cathode material is a ternary amorphous compound composite modified sodium-ion layered oxide cathode material, comprising: (1) Positive electrode material matrix; (2) Ternary amorphous compounds coated on the surface of the cathode material matrix; The general chemical formula of the ternary amorphous compound is Si. x B y Bi z M (1-x-y-z) O2; where 0.4 < x ≤ 0.7, 0.1 < y < 0.3, 0.1 < z < 0.3; 0 < 1 - xyz ≤ 0.1; M is one or more of Al, Zn, Li, Mg, and Ca.
[0023] The sodium-ion layered oxide cathode material of this invention has a core-shell structure, with the core being the cathode material matrix and the coating layer being a ternary amorphous compound. The near-surface crystal structure of the cathode material matrix is doped with Si, B, Bi, and M atoms. The multi-atom atoms of the ternary amorphous compound spontaneously dope into the near-surface crystal structure of the matrix material at high temperatures.
[0024] As one embodiment of the present invention, the mass ratio of the cathode material matrix to the ternary amorphous compound is 1:0.003~0.02.
[0025] As one embodiment of the present invention, the positive electrode material matrix is a sodium-electric layered oxide; Sodium-ionized layered oxides include NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, NaNi 0.316 Fe 0.316 Mn 0.316 Cu 0.05 O2, NaNi 0.306 Fe 0.306 Mn 0.306 Cu 0.05 Ti 0.03 At least one of O2.
[0026] As one embodiment of the present invention, the particle size of the positive electrode material matrix is 6~13μm.
[0027] The ternary amorphous compound of the present invention has a low softening temperature. The SiO2 inorganic oxide material has a melting point of 1713°C. After adding B2O3, the crystal structure can be transformed into a SiO2-B2O3 amorphous glass structure with disordered atomic arrangement at high temperature; however, the melting point of this binary amorphous glass material is still high, and the softening temperature exceeds 1600°C. The present invention adds Bi2O3 to the binary material to form a ternary amorphous material, which can significantly reduce the softening temperature. As the Bi content increases, the material’s thermal stability decreases and the softening temperature decreases. The softening temperature of the ternary amorphous material is less than 500°C. However, the Bi-containing ternary amorphous compound has a low melting point and poor chemical stability. Bi element is easily precipitated at high temperatures (above the softening temperature). This invention involves doping Si-B-Bi ternary materials with Zn, Ca, and Mg elements, which enhances the chemical and thermal stability of the amorphous material and also adjusts its softening temperature. Specifically, Li doping improves the high-temperature melt flowability and lowers the softening temperature of the amorphous material; Al doping significantly improves both the softening temperature and chemical stability. The low-temperature ternary material of this invention exhibits poor chemical stability; the introduction of doping elements balances the low-temperature melting performance and chemical stability of the amorphous material.
[0028] As one embodiment of the present invention, the positive electrode material matrix is prepared by the following method: According to the composition of the cathode material matrix, sodium source and transition metal precursor are weighed, mixed in the solid phase and calcined to obtain the cathode material matrix.
[0029] Sodium sources include either sodium carbonate or sodium hydroxide; Transition metal precursors include Ni 0.333 Fe 0.333 Mn 0.333 (OH)2, Ni 0.333 Fe 0.333 Mn 0.333 O 4 / 3 One of them; The stoichiometric ratio of sodium ions to transition metal precursors in the sodium source is 0.95~1.05:0.9~0.97.
[0030] The raw materials for preparing the cathode material matrix also include doped metal oxides; the doped metal oxides include one of CuO and TiO2.
[0031] The stoichiometric ratio of sodium ions, transition metal precursors, and doped element metal oxides in the sodium source is 0.95~1.05:0.9~0.97:0.03~0.1.
[0032] The solid-phase mixing speed is 1100~1300 rpm, and the time is 5~10 min. Solid-phase mixing is carried out using a planetary mixer.
[0033] The calcination temperature is 900~1050℃, and the calcination time is 8-12 hours. Calcination is carried out in an air atmosphere.
[0034] After cooling, the calcined product is ground and sieved to obtain a sodium-ion layered oxide cathode material matrix.
[0035] This invention also provides a method for preparing a modified cathode material (a ternary amorphous compound composite modified sodium ion layered oxide cathode material), comprising the following steps: The cathode material matrix and ternary amorphous compound (Si) x B y Bi z M (1-x-y-z) The O2 material is mixed in a solid phase, and the resulting mixture is calcined to obtain the modified cathode material.
[0036] As one embodiment of the present invention, the mass ratio of the cathode material matrix to the ternary amorphous compound is 1:0.003~0.02.
[0037] In one embodiment of the present invention, the solid-phase mixing speed is 1100~1300 rpm, and the time is 5-10 min. The solid-phase mixing is carried out in a planetary mixer.
[0038] In one embodiment of the present invention, the calcination temperature is 600~800℃, and the time is 3~8 hours. Calcination is carried out in an oxygen atmosphere.
[0039] As one embodiment of the present invention, the calcined product is cooled, ground, and sieved to obtain a modified cathode material.
[0040] This invention provides an application of the modified cathode material (a ternary amorphous compound composite modified sodium ion layered oxide cathode material) in the preparation of sodium ion battery cathodes.
[0041] This invention provides a sodium-ion battery cathode, including the modified cathode material (a ternary amorphous compound composite modified sodium-ion layered oxide cathode material).
[0042] The present invention provides a sodium-ion battery, including the positive electrode of the sodium-ion battery.
[0043] Compared with the prior art, the present invention has the following beneficial effects: 1. Structural advantages The ternary amorphous compound composite modified sodium-ion layered oxide cathode material prepared by this invention can synergistically improve performance.
[0044] (1) Structural stability: During the high-temperature post-processing, Si, B, Bi, M and other element ions in the partially molten amorphous compound will be embedded into the near-surface crystal structure of the oxide cathode material. The high-entropy strategy of multi-ion doping can enhance the oxygen bond energy of the transition metal, suppress the phase transition and lattice volume change that occur during the charging and discharging process of the O3 phase material, and reduce the lattice distortion caused by the Jahn-Teller effect of Mn in the cathode material matrix by multi-element high-entropy synergistic doping, thereby significantly improving the crystal structure stability of the material. (2) Interface stability & air stability: After the amorphous compound melts at high temperature, a dense amorphous coating layer is formed on the surface of the oxide cathode material. This coating layer can isolate the contact between the electrolyte and the cathode material, reduce the interfacial side reactions between the active material and the electrolyte, enhance the interfacial stability of the material, and improve the cycle performance of the material. In addition, the dense amorphous layer can inhibit the reaction between the surface of the layered oxide cathode material and H2O and CO2 in the air, inhibit the release of sodium from the material lattice, reduce the generation of residual alkali in the material, and effectively enhance the air stability of the material.
[0045] 2. Advantages of the preparation process The preparation method of this invention is simple, easy to operate and control, and uses low-cost raw materials, making it suitable for large-scale industrial production. The composite modification of cathode materials by ternary amorphous compounds can be achieved through simple solid-phase mixing followed by secondary sintering, avoiding damage to the cathode material matrix structure caused by high temperatures, and the process is easily scalable for mass production. Attached Figure Description
[0046] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings: Figure 1 This is an SEM image of the particle surface before material coating in Example 1; Figure 2 Here is an SEM image of the particle surface after material coating in Example 1; Figure 3 The XRD diffraction pattern of the ternary amorphous compound prepared in Example 1. Detailed Implementation
[0047] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. The following examples are implemented under the premise of the technical solution of the present invention, providing detailed implementation methods and specific operating procedures, which will help those skilled in the art to further understand the present invention. It should be noted that the scope of protection of the present invention is not limited to the following embodiments; any adjustments and improvements made under the concept of the present invention are all within the scope of protection of the present invention.
[0048] This invention provides a ternary amorphous compound-modified sodium-ion layered oxide cathode material, the preparation method of which includes the following steps: (1) Preparation of sodium-ion layered oxide cathode material matrix: Sodium source (such as sodium carbonate, sodium hydroxide) corresponding sodium ion element and transition metal precursor (such as Ni) 0.333 Fe 0.333 Mn 0.333 (OH)2) Doped element metal oxides were mixed in a stoichiometric ratio of 0.95~1.05:0.9~1:0~0.1 using a planetary mixer at 1200 rpm-5 min. The mixture was then placed in a muffle furnace and calcined at 900-1050℃ in air atmosphere for 8-12 h. After cooling, it was ground and sieved to obtain the sodium-electric layered oxide cathode material matrix. (2) Preparation of ternary amorphous compounds: according to the corresponding chemical formula Si x B y Bi z M (1-x-y-z)Weigh out the required molar amounts of elements for O2, including SiO2, B2O3, Bi2O3, and oxides of M doped elements. Mix the weighed compounds in a planetary mixer at 1500 rpm for 30 min for solid-phase mixing. Then, place the mixture in a muffle furnace and calcine it at 1300-1500℃ for 6-8 h in an air atmosphere. After the heat preservation is completed, slowly pour the high-temperature molten liquid into room temperature ultrapure water for rapid cooling and quenching. After cooling, grind and crush the product and put it into a ball mill for wet ball milling for 15 h. After ball milling, put it into an oven at 65℃ and dry it overnight. After drying, sieve it through a 500-mesh sieve to obtain a ternary amorphous compound. (3) High-temperature coating and curing of ternary amorphous compound onto the surface of sodium-electric layered oxide cathode material substrate: The cathode material substrate obtained in step 1 and the ternary amorphous compound Si x B y Bi z M (1-x-y-z) O2 material was mixed in a planetary mixer at a mass ratio of 1:0.003~0.02 for 1200 rpm-5 min. The mixture was then placed in a muffle furnace and calcined at 650~800℃ for 3~8 h in an oxygen atmosphere. After cooling, it was ground and sieved to obtain a ternary amorphous compound-modified sodium ion layered oxide cathode material.
[0049] The chemical raw materials used in the embodiments and comparative examples of this invention are all commercially available, as follows: Sodium carbonate: Jinghuang Technology (particle size D50=3μm); Ni, a transition metal precursor 0.333 Fe 0.333 Mn 0.333 (OH)2: GEM (particle size D50 = 4.5 μm): Nano copper oxide: Jinghuang Technology (particle size D50=30nm), JH-303; Titanium dioxide: Jinghuang Technology (particle size D50=200nm); SiO2: Evonik Industries (particle size D50=80nm); B2O3: Jinghuang Technology (particle size D50=1μm); Bi2O3: Jinghuang Technology (particle size D50=150nm); ZnO: Jinghuang Technology (particle size D50=300nm); Al2O3: Jinghuang Technology (particle size D50=20nm); MgO: Jinghuang Technology (particle size D50=100nm); CaO: Jinghuang Technology (particle size D50=600nm).
[0050] Example 1 This embodiment provides a ternary amorphous compound composite modified sodium-ion layered oxide cathode material, wherein the cathode material matrix is a conventional matrix NaNi. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, the ternary amorphous compound is Si 0.65 B 0.15 Bi 0.15 Zn 0.05 O2.
[0051] (1) Positive electrode material matrix NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Preparation of O2: Sodium carbonate and transition metal precursor Ni 0.333 Fe 0.333 Mn 0.333 (OH)₂ was solid-phase mixed at a stoichiometric ratio of 0.5:1 using a planetary mixer at 1200 rpm for 5 min. The mixture was then calcined in a muffle furnace at 1000 °C for 9 h in air. After cooling, it was ground and sieved to obtain the sodium-ion layered oxide cathode material matrix NaNi. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 (particle size 10 μm), SEM image as follows Figure 1 As shown; (2) Ternary amorphous compound Si 0.65 B 0.15 Bi 0.15 Zn 0.05 Preparation of O2: SiO2, B2O3, Bi2O3, and ZnO were weighed according to an elemental molar ratio of 0.65:0.15:0.15:0.05. The weighed compound was stirred in a planetary mixer at 1500 rpm for 30 min for solid-phase mixing. The mixture was then placed in a muffle furnace and calcined at 1500℃ for 6 h in air atmosphere. After holding at this temperature, the high-temperature molten liquid was slowly poured into ultrapure water at room temperature (25℃) for rapid cooling and quenching. After cooling, the product was ground and crushed, then wet ball-milled at 100 rpm for 15 h. After ball milling, it was dried in an oven at 65℃ overnight. After drying, it was sieved to obtain a ternary amorphous compound with a particle size of 1 μm and a softening temperature of 450~600℃. The XRD diffraction pattern is shown below. Figure 3 As shown, the diffraction shows significant amorphous diffraction peaks, indicating that the oxide is an amorphous material after synthesis. (3) Preparation of sodium-ion layered oxide cathode material modified by ternary amorphous compound composite: High-temperature coating and curing of ternary amorphous compounds onto the surface of sodium-electric layered oxide cathode material substrate: The cathode material substrate obtained in steps 1 and 2 and the ternary amorphous compound Si are coated and cured onto the surface of the sodium-electric layered oxide cathode material substrate. 0.65 B 0.15 Bi 0.15 Zn 0.05 O2 material was mixed in a planetary mixer at a set mass ratio of 1:0.008 for 1200 rpm for 5 min. The mixture was then calcined in a muffle furnace at 650 °C for 4 h under an oxygen atmosphere. After cooling, it was ground and sieved to obtain a ternary amorphous compound-modified sodium-ion layered oxide cathode material. SEM images are shown below. Figure 2 As shown.
[0052] Depend on Figure 1 , Figure 2 It can be seen that after the amorphous compound is coated, a uniform nano-island coating layer is formed on the surface of the material, the particle size does not change significantly, and the impurities on the particle surface are significantly reduced.
[0053] Example 2 This embodiment provides a ternary amorphous compound-modified sodium-ion layered oxide cathode material, wherein the cathode material matrix is a 5% Cu-doped NaNi matrix. 0.316 Fe 0.316 Mn 0.316 Cu 0.05 O2, the ternary amorphous compound is Si 0.65 B 0.15 Bi 0.15 Zn 0.05 O2.
[0054] The preparation method is basically the same as in Examples 1 and 2, except that the cathode material matrix is replaced with NaNi. 0.316 Fe 0.316 Mn 0.316 Cu 0.05 O2.
[0055] NaNi 0.316 Fe 0.316 Mn 0.316 Cu 0.05 O2 preparation steps: Sodium carbonate and transition metal precursor Ni 0.333 Fe 0.333 Mn 0.333 (OH)₂ and nano-copper oxide were mixed in a stoichiometric ratio of 0.5:0.475:0.05 using a planetary mixer at 1200 rpm for 5 min. The mixture was then calcined in a muffle furnace at 1000 °C for 9 h in air. After cooling, the mixture was ground and sieved to obtain the sodium-ion layered oxide cathode material matrix NaNi. 0.316 Fe0.316 Mn 0.316 Cu 0.05 O2.
[0056] Example 3 This embodiment provides a ternary amorphous compound-modified sodium-ion layered oxide cathode material, wherein the cathode material matrix is a NaNi matrix doped with 5% Cu and 3% Ti. 0.306 Fe 0.306 Mn 0.306 Cu 0.05 Ti 0.03 O2, the ternary amorphous compound is Si 0.65 B 0.15 Bi 0.15 Zn 0.05 O2.
[0057] The preparation method is basically the same as in Example 1, except that the cathode material matrix is replaced with NaNi. 0.306 Fe 0.306 Mn 0.306 Cu 0.05 Ti 0.03 O2.
[0058] NaNi 0.306 Fe 0.306 Mn 0.306 Cu 0.05 Ti 0.03 O2 preparation steps: Sodium carbonate and transition metal precursor Ni 0.333 Fe 0.333 Mn 0.333 (OH)₂, nano-copper oxide, and titanium dioxide were mixed in a stoichiometric ratio of 0.5:0.46:0.05:0.03 using a planetary mixer at 1200 rpm for 5 min. The mixture was then calcined in a muffle furnace at 1000 °C for 9 h in air. After cooling, the mixture was ground and sieved to obtain the sodium-ion battery layered oxide cathode material matrix NaNi. 0.306 Fe 0.306 Mn 0.306 Cu 0.05 Ti 0.03 O2.
[0059] Example 4 This embodiment provides a ternary amorphous compound composite modified sodium-ion layered oxide cathode material, wherein the cathode material matrix is a conventional matrix NaNi. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, the ternary amorphous compound is Si 0.7 B 0.15 Bi 0.1 Al0.05 O2.
[0060] The preparation method is basically the same as in Example 1, except that the ternary amorphous compound is replaced with Si. 0.7 B 0.15 Bi 0.1 Al 0.05 O2 (the oxide raw materials are SiO2, B2O3, Bi2O3, and Al2O3).
[0061] Example 5 This embodiment provides a ternary amorphous compound composite modified sodium-ion layered oxide cathode material, wherein the cathode material matrix is a conventional matrix NaNi. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, the ternary amorphous compound is Si 0.55 B 0.25 Bi 0.1 Zn 0.05 Mg 0.05 O2.
[0062] The preparation method is basically the same as in Example 1, except that the ternary amorphous compound is replaced with Si. 0.55 B 0.25 Bi 0.1 Zn 0.05 Mg 0.05 O2 (the oxide raw materials are SiO2, B2O3, Bi2O3, ZnO, and MgO).
[0063] Example 6 This embodiment provides a ternary amorphous compound composite modified sodium-ion layered oxide cathode material, wherein the cathode material matrix is a conventional matrix NaNi. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, the ternary amorphous compound is Si 0.6 B 0.2 Bi 0.15 Li 0.05 O2.
[0064] The preparation method is basically the same as in Example 1, except that the ternary amorphous compound is replaced with Si. 0.6 B 0.2 Bi 0.15 Li 0.05 O2 (the oxide raw materials are SiO2, B2O3, Bi2O3, and Li2O).
[0065] Example 7 This embodiment provides a ternary amorphous compound composite modified sodium-ion layered oxide cathode material, wherein the cathode material matrix is a conventional matrix NaNi.1 / 3 Fe 1 / 3 Mn 1 / 3 O2, the ternary amorphous compound is Si 0.65 B 0.15 Bi 0.15 Zn 0.05 O2 (the oxide raw materials are SiO2, B2O3, Bi2O3, and ZnO).
[0066] The preparation method is basically the same as in Example 1, except that the ternary amorphous compound is replaced with Si. 0.65 B 0.15 Bi 0.15 Zn 0.05 O2.
[0067] Example 8 This embodiment provides a ternary amorphous compound composite modified sodium-ion layered oxide cathode material, wherein the cathode material matrix is a conventional matrix NaNi. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, the ternary amorphous compound is Si 0.45 B 0.25 Bi 0.25 Ca 0.05 O2 (the oxide raw materials are SiO2, B2O3, Bi2O3, and CaO).
[0068] The preparation method is basically the same as in Example 1, except that the ternary amorphous compound is replaced with Si. 0.45 B 0.25 Bi 0.25 Ca 0.05 O2.
[0069] Example 9 This embodiment provides a ternary amorphous compound composite modified sodium-ion layered oxide cathode material, wherein the cathode material matrix is a conventional matrix NaNi. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, the ternary amorphous compound is Si 0.55 B 0.20 Bi 0.15 Mg 0.05 Ca 0.05 O2 (the oxide raw materials are SiO2, B2O3, Bi2O3, MgO, and CaO).
[0070] The preparation method is basically the same as in Example 1, except that the ternary amorphous compound is replaced with Si. 0.55 B 0.20 Bi 0.15 Mg 0.05 Ca 0.05 O2.
[0071] Example 10 This embodiment provides a ternary amorphous compound-modified sodium-ion layered oxide cathode material. The preparation method is basically the same as that in Example 1, except that in step (3), the cathode material matrix and the ternary amorphous compound Si 0.65 B 0.15 Bi 0.15 Zn 0.05 The mass ratio of O2 material is 1:0.003.
[0072] Example 11 This embodiment provides a ternary amorphous compound-modified sodium-ion layered oxide cathode material. The preparation method is basically the same as that in Example 1, except that in step (3), the cathode material matrix and the ternary amorphous compound Si 0.65 B 0.15 Bi 0.15 Zn 0.05 The mass ratio of O2 materials is 1:0.02.
[0073] Comparative Example 1 This embodiment provides a sodium-ion layered oxide cathode material, which is an uncoated substrate NaNi. 1 / 3 Fe 1 / 3Mn 1 / 3 O2 refers to the positive electrode material matrix prepared in step (1) of Example 1.
[0074] Comparative Example 2 This embodiment provides a sodium ion layered oxide cathode material, which is an uncoated substrate Na. 0.98 Ni 0.31 6Fe 0.316 Mn 0.316 Cu 0.05 O2 refers to the positive electrode material matrix prepared in step (1) of Example 2.
[0075] Comparative Example 3 This embodiment provides a sodium-ion layered oxide cathode material, which is an uncoated substrate NaNi. 0.306 Fe 0.306 Mn 0.306 Cu 0.05 Ti 0.03 O2 refers to the positive electrode material matrix prepared in step (1) of Example 3.
[0076] Comparative Example 4 This embodiment provides a sodium ion layered oxide cathode material, the preparation method of which is basically the same as that in Example 1, the only difference being that the coating material Si is used. 0.65 B 0.15 Bi0.15 Zn 0.05 O2 is replaced with equal amounts of oxides: SiO2, B2O3, Bi2O3, ZnO.
[0077] Comparative Example 5 This embodiment provides a sodium ion layered oxide cathode material, the preparation method of which is basically the same as that in Example 1, the only difference being that the coating material Si is used. 0.65 B 0.15 Bi 0.15 Zn 0.05 O2 is replaced with an equal amount of Si 0.65 B 0.3 Zn 0.05 O2.
[0078] The amorphous compounds formed by lacking Bi have a high softening temperature (>1300℃). During the process of coating the substrate surface, the amorphous compounds do not form a low-temperature melt flow dynamic, resulting in poor coating effect and failure to incorporate some amorphous compound elements into the surface. Ultimately, the material has poor air stability and cycling performance.
[0079] Comparative Example 6 This embodiment provides a sodium ion layered oxide cathode material, the preparation method of which is basically the same as that in Example 1, the only difference being that the coating material Si is used. 0.65 B 0.15 Bi 0.15 Zn 0.05 The oxide of B in O2 is replaced with an equal amount of oxide of Bi.
[0080] The absence of element B prevents the construction of Si-B amorphous glass structures, resulting in the final product obtained from the preparation of amorphous compounds in step two still being an oxide mixture, with an actual coating effect similar to that of Comparative Example 4.
[0081] Comparative Example 7 (Bi replaced with Al) This embodiment provides a sodium ion layered oxide cathode material, the preparation method of which is basically the same as that in Example 4, the only difference being that the coating material Si is used... 0.65 B 0.15 Bi 0.15 Zn 0.05 O2 is replaced with an equal amount of Si 0.7 B 0.15 Al 0.15 O2.
[0082] Similar to Comparative Example 5, the lack of Bi element lowers the melting point of the amorphous compound. At the coating temperature of 650℃~800℃, the amorphous compound cannot achieve a low-temperature melting effect, resulting in a poor coating effect on the substrate.
[0083] Comparative Example 8 This embodiment provides a sodium ion layered oxide cathode material, the preparation method of which is basically the same as that in Example 1, the only difference being that the coating material Si is used. 0.65 B 0.15 Bi 0.15 Zn 0.05 The oxide of B in O2 is replaced with an equal amount of oxide of Li.
[0084] Similar to Comparative Example 6, the lack of element B prevents Si-Li from constructing an amorphous glass structure, resulting in an oxide mixture with a coating effect similar to that of Comparative Example 6.
[0085] Comparative Example 9 This embodiment provides a sodium ion layered oxide cathode material, and the preparation method is basically the same as that in Example 1, except that the calcination temperature in step 3 is 500℃.
[0086] The cathode material substrates and ternary amorphous compound coatings of the embodiments and comparative examples are shown in Table 1 below: Table 1
[0087] Test method: The cathode materials obtained from the examples and comparative examples were assembled into CR2032 coin cells and electrochemical tests were performed. The assembly sequence was as follows: the cathode material, conductive agent (conductive carbon black), and polyvinylidene fluoride were mixed at a mass ratio m (96:2:2) to prepare a slurry, wherein PVDF was mixed with NMP beforehand. After the slurry was mixed, it was evenly coated onto aluminum foil using a coating machine and placed in an electric heating drying oven at 120°C overnight to dry the cathode sheet completely. The next step was to compact the cathode sheet with rollers and cut it into 12mm round pieces, and record the mass of each round piece. The coin cell half-cells used for testing the cathode material were assembled in a super-clean glove box with Ar, H2O, and O2 protective atmospheres controlled within set ranges. The electrolyte composition consisted of sodium hexafluorophosphate (NaPF6) as the sodium salt (1 mol / L), ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a 1:1:1 mass ratio, with the addition of 0.5 wt% fluoroethylene carbonate (FEC). The cells were packaged in the correct order, with 8 ml of electrolyte added. After assembly, the cells were allowed to stand for 4 hours to activate them before electrochemical testing. The assembled coin cell was cyclically charged and discharged using a constant current and constant voltage charging method followed by constant current discharging. The cutoff voltage range of the coin cell during the charging and discharging process was 2.0-4.1V, and the current density was 12mA / g at 0.1C and 120mA / g at 1C.
[0088] The performance data of the examples and comparative examples are shown in Table 2: Table 2
[0089] The above examples and comparative examples fully demonstrate that the ternary amorphous compound composite modified sodium-ion layered oxide cathode material prepared by the present invention achieves simultaneous improvement in material cycle performance, interface stability and air stability through the high-entropy doping strategy and the synergistic effect of the amorphous coating layer, and has significant advantages and good application prospects.
[0090] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. The application of a ternary amorphous compound in the preparation of modified cathode materials; the application involves coating the ternary amorphous compound onto the surface of a cathode material matrix; The general chemical formula of the ternary amorphous compound is Si. x B y Bi z M (1-x-y-z) O2; among which, 0.4 < x ≤ 0.7, 0.1 < y < 0.3, 0.1 < z < 0.3; 0 < 1 - xyz ≤ 0.1; M is one or more of Al, Zn, Li, Mg, and Ca.
2. The application according to claim 1, characterized in that, The particle size of the ternary amorphous compound is 0.1~2μm.
3. The application according to claim 1, characterized in that, The softening temperature of the obtained ternary amorphous compound is 350~620℃.
4. The application according to claim 1, characterized in that, The ternary amorphous compound is prepared by the following method: according to the required molar amounts of elements in the chemical formula, the oxides of SiO2, B2O3, Bi2O3 and M doping elements are mixed in solid phase and then calcined. The resulting molten liquid is cooled, quenched and pulverized to obtain the ternary amorphous compound.
5. The application according to claim 4, characterized in that, Calcination is carried out in an air atmosphere; And / or, the calcination temperature is 1300~1500℃; And / or, the calcination time is 6-8 hours; And / or, cooling quenching involves pouring molten liquid into water.
6. A modified cathode material, characterized in that, include: (1) Positive electrode material matrix; (2) Ternary amorphous compounds coated on the surface of the cathode material matrix; The general chemical formula of the ternary amorphous compound is Si. x B y Bi z M (1-x-y-z) O2; where 0.4 < x ≤ 0.7, 0.1 < y < 0.3, 0.1 < z < 0.3; 0 < 1 - xyz ≤ 0.1; M is one or more of Al, Zn, Li, Mg, and Ca.
7. The modified cathode material according to claim 6, characterized in that, The near-surface crystal structure of the cathode material matrix is doped with Si, B, Bi, and M atoms; And / or, the mass ratio of the cathode material matrix to the ternary amorphous compound is 1:0.003~0.02; And / or, the positive electrode material matrix is a sodium-electric layered oxide; And / or, the particle size of the positive electrode material matrix is 6~13μm.
8. A method for preparing the modified cathode material according to any one of claims 6-7, characterized in that, Includes the following steps: Modified cathode materials are obtained by solid-state mixing and calcination of the cathode material matrix and ternary amorphous compound.
9. The method for preparing the modified cathode material according to claim 8, characterized in that, The calcination temperature is 600-800℃; And / or, the calcination time is 3~8 hours; And / or, calcination is carried out in an oxygen atmosphere.
10. The application of the modified cathode material as described in any one of claims 6-7 in the preparation of a sodium-ion battery cathode.
11. A sodium-ion battery positive electrode, characterized in that, The cathode of a sodium-ion battery includes the modified cathode material as described in any one of claims 6-7.
12. A sodium-ion battery, characterized in that, The sodium-ion battery includes the sodium-ion battery positive electrode as described in claim 11.